Designing Mobile Games Application for Digitalization of English Teaching and Learning Materials for Elementary School - Rofi'i, Agus; Sumartini, Sri; Susilo, Sigit Vebrianto; Tundreng, Syarifuddin (Universitas Pendidikan Ganesha, 2023)
The world faces rapid industrial changes in line with the industrial revolution 4.0. These changes leave several challenges and opportunities to be adaptive and evolve to respond to the challenges of the times. Therefore, this research aims to develop Android-based digital teaching materials to support learning mobility. This study uses a research development (R&D) approach. The instructional design used in this study is the research model of Gall. The research method used is mixed methods research. Furthermore, the type of design that will be used exploratory type. The research started with qualitative research activities aimed at exploring the learning process and testing the hypothesis through experimental research. Experimental research will provide a decision about the acceptability or not of the hypotheses that developed to be widely applied in elementary schools. The study results showed that digital teaching materials based on Android games have been successfully developed and implemented correctly; this teaching material also helps them understand the material being taught. Digitizing teaching materials through mobile learning can be an effective alternative to improving English learning in elementary schools.